2014
DOI: 10.1016/j.jcat.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Supported iron nanoparticles for the hydrodeoxygenation of microalgal oil to green diesel

Abstract: Iron nanoparticles supported on mesoporous silica nanoparticles (Fe-MSN) catalyze the hydrotreatment of fatty acids with high selectivity for hydrodeoxygenation over decarbonylation and hydrocracking. The catalysis is likely to involve a reverse Mars-Van Krevelen mechanism, in which the surface of iron is partially oxidized by the carboxylic groups of the substrate during the reaction. The strength of the metal-oxygen bonds that are formed affects the residence time of the reactants facilitating the successive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 41 publications
2
84
0
Order By: Relevance
“…These materials are interesting because of their ability to disperse the active phase and their suitable structure for the diffusion of large molecules, such as those present in vegetable oils (Stöcker, 2008). For instance, mesoporous silica nanoparticles have been proven as effective catalyst supports for upgrading microalgae oil using iron nanoparticles (Kandel et al, 2014). Furthermore, stearic acid deoxygenation on Pd/SBA-15 and Pd/C catalysts showed a higher turnover frequency in the case of Pd/SBA-15, indicating the effectiveness of the mesoporous support (Lestari et al, 2010).…”
Section: Role Of Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are interesting because of their ability to disperse the active phase and their suitable structure for the diffusion of large molecules, such as those present in vegetable oils (Stöcker, 2008). For instance, mesoporous silica nanoparticles have been proven as effective catalyst supports for upgrading microalgae oil using iron nanoparticles (Kandel et al, 2014). Furthermore, stearic acid deoxygenation on Pd/SBA-15 and Pd/C catalysts showed a higher turnover frequency in the case of Pd/SBA-15, indicating the effectiveness of the mesoporous support (Lestari et al, 2010).…”
Section: Role Of Supportmentioning
confidence: 99%
“…Even in the case of Pd/C catalysts that remove oxygen exclusively through DCO under either inert or hydrogen atmospheres Lestari et al, 2009b), hydrogen has been shown to influence the kinetics of deoxygenation and improve the activity and stability of the catalyst (Immer et al, 2010;Rozmysłowicz et al, 2012). Elevated hydrogen pressures ensure higher carbon yields in the diesel range by suppressing side reactions such as cracking and decarboxylation (Kandel et al, 2014). In addition, hydrogen has been found to benefit catalyst stability by preventing cokeforming oligomerization reactions through hydrogenation of coke precursors, i.e., unsaturated hydrocarbons (Do et al, 2009).…”
Section: Pressure (H2 Pressure)mentioning
confidence: 99%
“…This transformation is usually realized in more than one step involving the rate determining step. This is the reason for which in many cases carboxylic acids are used as probe molecules instead of plant oils or monoesters [92][93][94][95][96]. A detailed description of the SDO reaction pathways will be presented in a subsequent section, mainly with respect to the nickel based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst for hydrodeoxygenation of lipids mainly includes Co [8], Mo [9], W [10], Fe [11], or precious metals [12][13][14][15]. Conventional supported catalysts mainly use inert silica, alumina, and carbon as supports.…”
Section: Introductionmentioning
confidence: 99%